(untitled) (Indian Journal of Public Health Research & Development, 2023)
Sustainable Development Goal number three advocates for a healthy life for all and a significant part of achieving this is the availability of Doctors across all landscapesequitably. But there has been a lack of healthcare force, particularly in rural areas. The medical curriculum in India is exhaustive and emphasizes the need for higher education than serving as medical officers in primary health centers. Many aspects of undergraduate teaching are rarely utilized, if at all. So it’s high time to relook at our MBBS curriculum to incorporate more practical real-life education needed for managingprimary health centers and cutting the extra burden.